The Influence of Political, Social, and Economic Factors on the Acceptance of Technology in the Workplace in the Context of Industrial Revolution 4.0 - Nicoleta Cristache; Nicoleta Valentina Florea; Marian Năstase; Gabriel Croitoru; Costinela Fortea; Manuela-Violeta Tureatca (Amfiteatru Economic, 2025)
This article explores the role of Industrial Revolution 4.0 in transforming the labour market, analysing the impact of political, economic, and social factors on the acceptance of technology in the workplace, leading to the demand for new professional skills and the digitisation of traditionally performed jobs. Through an analysis based on a sample of 286 respondents, as well as the use of IBM SPSS Statistics 27 and SmartPLS 4.1.0.8 software, we were able to validate the four formulated hypotheses and gain an in-depth understanding of the interconnections between these factors. The results suggest that political and social factors have a significant impact on technology acceptance, while the influence of economic factors, although essential, is more limited. Furthermore, the strong positive effect of technological factors on labour market performance is highlighted, highlighting the importance of technology adoption to improve organisational efficiency. The study findings suggest the need for an integrated approach that includes supportive policies, educational initiatives, and inclusive social practices to maximise technological benefits. Practical implications for managers focus on developing support strategies for innovation and promoting an organisational culture capable of sustaining continuous learning. Thus, this study contributes to understanding of the complex dynamics of technology acceptance and labour market performance in the era of Industry 4.0.